Emergence of proto-organisms from bistable stochastic differentiation and adhesion. - Durán-Nebreda, Salva; Bonforti, Adriano; Montañez, Raúl; Valverde, Sergi; Solé, Ricard V. (The Royal Society, 2016)
The rise of multicellularity in the early evolution of life represents a major challenge for evolutionary biology. Guidance for finding answers has emerged from disparate fields, from phylogenetics to modelling and synthetic biology, but little is known about the potential origins of multicellular aggregates before genetic programmes took full control of developmental processes. Such aggregates should involve spatial organization of differentiated cells and the modification of flows and concentrations of metabolites within well-defined boundaries. Here, we show that, in an environment where limited nutrients and toxic metabolites are introduced, a population of cells capable of stochastic differentiation and differential adhesion can develop into multicellular aggregates with conflict mediation mechanisms and a complex internal structure. The morphospace of possible patterns is shown to be very rich, including proto-organisms that display a high degree of organizational complexity, far beyond simple heterogeneous populations of cells. Our findings reveal that there is a potentially enormous richness of organismal complexity between simple mixed cooperators and embodied living organisms.
https://openpolicyfinder.jisc.ac.uk/id/publication/11598
Keywords: Evolución (Biología); Paleobiología evolutiva; Complexity; Evolution; Major transitions; Multicellularity